Physico-Chemical Properties of Fiber Extracted from the Flower of Celosia Argentea Plant - P. Manimaran; M. R. Sanjay; P. Senthamaraikannan; S. S. Saravanakumar; Suchart Siengchin; G. Pitchayyapillai; Anish Khan (Journal of Natural Fibers, 2021)
This study was aimed at understanding the characteristics of Celosia argentea fiber (CAF) and its physicochemical properties. The physicochemical properties of CAF were analyzed by FT-IR, XRD, TGA, SEM, and AFM analysis. Cellulose content (64.34wt.%), density (843 kg/m3) and crystallinity index (52.54%) properties were identified in the CAF while the thermal studies performed by TG and DTG technique revealed that the maximum degradation temperature is 324°C with a kinetic activation energy of 61.393 kJ/mol. From the results, it is evident that the CAF could be one of the future reinforcement materials for green composites applications.